The Effect of Islamic Microfinance on Poverty Alleviation: Study in Indonesia - Wahibur Rokhman (Economic Review: Journal of Economics and Business, 2013)
This study was conducted to examine the role of Islamic microfinance on poverty alleviation. The four indicators of poverty alleviation were used: income levels, children's education, health care, and business progress. This study used the sample of 150 borrowers from 20 Islamic microfinance institutions in Central Java, Indonesia. The questionnaires were distributed to them using the purposive sampling method. Out of 150 questionnaires distributed, the researchers received back 124 responses. The empirical tests indicated that microfinance has a significant role on improving income level, children's education, and business progress. However, the study did not find any significant role of microfinance in access to health care. Implications, limitations and suggestions for future research are discussed.
Keywords: G21; I32; 330; Islamic microfinance; Poverty alleviation; Indonesia